Nutritional Status of Children (5 - 18 Years) by Using Anthropometric Indices: A Cross-Sectional Study Among the Sartang and Miji, Lesser Known Tribes of Arunachal Pradesh, India - Ashgar, Md.; Amung, Radhe; Chakrabarty, Suman (Journal of Nepal Paediatric Society, 2021)
Introduction: In this era of globalization, planners often fail to understand the importance of community specific nutritional intervention among children due to dearth of study specifically among the lesser known communities in tribal dominated Indian state like Arunachal Pradesh. In order to find out the present condition of nutritional status in such lesser known tribal groups in the state, this present cross-sectional study was conceptualized to assess the nutritional status by using anthropometric indices in the Sartang and Miji tribal children in Arunachal Pradesh, India. Methods: A total of 452 children aged five to 18 years living in rural areas of West Kameng district of Arunachal Pradesh, India were considered for the present analysis. The international standards were used to collect height and weight data and height for age and BMI for age percentile were calculated. Results: The results revealed that the prevalence of stunting (< - 2 SD height for age) was higher among the Sartang male (34.0%) and female (46.3%) compared to Miji male (26.7%) and female (23.1%), respectively. Conversely the prevalence of overweight (percentile of BMI for age > 85) was also higher among the Sartang male (19.1%) and female (27.8%) compared to Miji children. It may be due to the alteration of traditional food habits, consumption of regular fast food and increasing less socio-economic equity and higher inequality in both the communities. Conclusions: Therefore, undernutrition as well as over nutrition are prevalent among studied children perhaps correlated with rapid change in their food habits and lifestyle in the early age.